The Effectiveness Of Puperial Exercise And OxcytocinMassage Againts Uterine Involusi In PostpartumMother At The Clinic - Meria Turnip; Elvi Era Liesmayani; Sri Putriani Sinaga; Desika Wali Pardede (JURNAL KEBIDANAN KESTRA (JKK), 2026)
Uterine involution is an important physiological process after childbirth that indicates the recovery of the uterus to its normal size and function. However, suboptimal involution can cause serious complications in postpartum mothers. Non-pharmacological approaches, specifically postpartum exercise and oxytocin massage, are recognized for their potential to facilitate uterine involution. This study aims to evaluate the efficacy of these two interventions among postpartum mothers at the Matahari Pratama Clinic. Adopting a quasi-experimental framework with a two-group pretest-posttest design, the research involved 20 participants divided equally into two intervention groups. Uterine involution progress was systematically monitored both prior to and following the administration of either postpartum exercise or oxytocin massage. The results 1showed that before the intervention, 7 respondents (70%) experienced abnormal uterine involution. After being given postpartum exercise, the number of respondents experiencing normal uterine involution increased to 7 people (70%). Meanwhile, after oxytocin massage, 6 respondents (60%) showed normal uterine involution conditions. The findings suggest that both postpartum exercise and oxytocin massage significantly facilitate the acceleration of uterine involution. This effectiveness is statistically supported by a significance value of (p < 0.05), confirming that these non-pharmacological interventions are viable methods for enhancing postpartum recovery. However, postpartum gymnastics has been shown to provide more optimal results than oxytocin massage. Therefore, these two interventions are recommended to be implemented routinely in postpartum care as an effort to accelerate the process of uterine involution and prevent complications.